2011
DOI: 10.1111/j.1365-2907.2011.00203.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypsodonty and tooth facet development in relation to diet and habitat in herbivorous ungulates: implications for understanding tooth wear

Abstract: 1. The evolution of high-crowned teeth or hypsodonty in herbivorous mammals is widely interpreted as a species-specific adaptation to increasingly wear-inducing diets and environments at evolutionary time scales, with internal abrasives (such as phytoliths in grasses) and/or external abrasives (such as dust or grit) as putative causative factors. The mesowear score (MS) instead describes tooth wear experienced by individual animals during their lifetime. 2. Under the assumption that the abrasiveness that cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
127
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 160 publications
(142 citation statements)
references
References 68 publications
8
127
1
6
Order By: Relevance
“…Although we are unable to challenge the adaptive value of hypsodonty from the fossil pollen analysis, we demonstrate quantitatively that grasslands per se were virtually absent prior to Quaternary in Patagonia: thus, whatever the results of the microwear analysis, these animals could not have been eating grass. Kaiser et al 30 showed that external abrasives of very fine particle size have a major role in naturally occurring tooth wear, which is consistent with the view of Pascual and Ortiz Jaureguizar 31 , who interpreted precocious hypsodonty in South American ungulates as an effective response to abrasive volcanic ash that may had dusted the leaves of plants.…”
Section: Nature Communications | Doi: 101038/ncomms2299supporting
confidence: 55%
“…Although we are unable to challenge the adaptive value of hypsodonty from the fossil pollen analysis, we demonstrate quantitatively that grasslands per se were virtually absent prior to Quaternary in Patagonia: thus, whatever the results of the microwear analysis, these animals could not have been eating grass. Kaiser et al 30 showed that external abrasives of very fine particle size have a major role in naturally occurring tooth wear, which is consistent with the view of Pascual and Ortiz Jaureguizar 31 , who interpreted precocious hypsodonty in South American ungulates as an effective response to abrasive volcanic ash that may had dusted the leaves of plants.…”
Section: Nature Communications | Doi: 101038/ncomms2299supporting
confidence: 55%
“…First, a body of work has shown that hypsodonty in modern ungulates correlates not just with diet, but with habitat openness, precipitation and feeding height, regardless of grass abundance [27][28][29] ; thus, there is current utility of high-crowned teeth in environments where abundant abrasives, such as soil particles or volcanic ash, are ingested alongside plant matter. In particular, a recent study implies that fine-grained volcanic ash abrades teeth without resulting in the wear patterns associated with ingestion of coarser grit 27 . Second, although high levels of ingested grit are typically associated with open, arid ecosystems, large mesodont-hypsodont herbivores do exist in some forest or woodland habitats today ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological adaptations improving wear resistance of herbivorous mammal teeth, such as increased molar crown height (hypsodonty), reflect the conditions under which they evolved and have been shown to be adaptive both to environmental factors (such as precipitation and erosion rates, which regulate the accumulation of mineral particles on plant material), as well as to dietary factors (abrasive food items, mainly grass). The mesowear signal, on the other hand, has been demonstrated to show a purely dietary signal (nonabrasive vs. abrasive plant material, or browse vs. grass) (Louys et al, 2012;Kaiser et al, 2013;Kubo and Yamada, 2014). Mesowear analysis will thus provide a robust proxy for ungulate diet irrespective of abiotic environmental and climatic effects.…”
Section: Mesowear Analysismentioning
confidence: 99%